The Implementation of Good Corporate Governance to Develop Islamic Micro Insurance In Indonesia - Irman Firmansyah (IQTISHADIA, 2019)
This study is aimed to find the best model in order to create Good Corporate Governance (GCG) for Islamic micro insurance development. The research methodology employed in this study was Analytic Network Process (ANP) using quantitative and qualitative approaches. The informants of this consist of practitioners, academia, and researchers who have good understanding of the problem. The finding of this study shows that the priority to embody good corporate governance principle in order to develop Islamic micro insurance in Indonesia namely, responsibilities, followed by equality and fairness, independences, accountability and transparency. In addition, the priorities of strategies that can be implemented to optimize GCG implementation are training and education for human resources, followed by focus on internal control mechanism, and the third is good corporate governance implementation in each level. The finding of this study also contributed to the best model of good corporate governance model to enhance Islamic micro insurance in Indonesia.